Dilematika Sengketa Pertanahan dan Penyelesaiannya dalam Perspektif Hukum Positif - Iswantoro Iswantoro (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2013)
Problems of land disputes issues from time to time increased both the qualityand quantity. The reason is because the needs of an increasingly complex use of land,while land availability is very limited. Besides, the cause can be triggered by the government regulations that make legislation happen to overlap and disharmony in the implementation. This problem coupled with a lack of understanding of the law in society as a result of acts committed against the land he owned, and the publication of the registration system which adopts negative publicity, making the lawsuit and opening faucets to objections from other parties on the ground that have been registered. The inequality in land ownership, and the rights of dual certificates and land use that doesnot comply with the permit location, allocation, use, and make use of the land into the complex problems of land disputes.It is also encouraged in the historical experience of our long agrarian law as aresult of government policy that has a tendency that the land be used for a political commodity. It should be understood as well the condition of land administration in times past were less orderly also be a driving force of land disputes. With this condition need to be made as a container seeking justice, legal protection and law enforcement, namely the judiciary for its container. Besides settling land disputes can malalui administrative channels that BPN, and Mediation, Reconciliation and ADR, which greatly contributed to the completion of their work land disputes. Therefore necessary stakeholders so that these ideals can be realized.